Spirit Tari Wali Topeng Sidhakarya dalam Meningkatkan Prestasi Atlet Provinsi Bali pada PON 2021 di Papua - I Gusti Ngurah Putra Eka Santosa (Universitas Udayana, 2022)
There is ample evidence to suggest that dancing and exercise can provide the same health benefits. This article discusses the benefits of the Sidhakarya Sacred Mask Dance spirit in improving the performance of Balinese athletes. It was investigated to see the increase in the performance of the Klungkung Regency petanque athletes who skyrocketed sharply after applying the Sidhakarya state conditioning method as an additional from the usual routine exercise. This study uses an observation method that was conducted during the training centre of athletes who were going to compet in the XX PON which was held in Papua. The analysis shows that athletes who start training with Sidhakarya Dance self-conditioning experience increased self-confidence, better mastery of skills, can control emotions and are able to implement strategies set by the coach better. This article contributes that the Sidhakarya Sacred Mask Dance spirit is useful in contemporary life in the field of sports